Profile of Attitudes of Science Teacher Candidates Towards Indigenous Science-Based Science Learning - Agus Muliadi; Joni Rokhmat; Aliefman Hakim; AA Sukarso (IKIP Mataram, 2023)
The study aims to explore the attitudes of science teacher candidates towards indigenous science-based science learning. This study is an exploratory research conducted in three study programs that provide science teacher education, namely Biology, Chemistry, and Physics Education with 53 research subjects. This study uses a research instrument in the form of a closed questionnaire with answers using a Likert scale and has been validated by experts. The research data were analyzed using quantitative descriptive statistics and inferential statistics Anova test and t-test. The results of this study are (1) the attitude of students in the biology education study program has an average score of 3,29 in the Good category, physics education is 3,00 in the Good category, and chemistry education is 3,13 in the Good category; (2) the attitude of male students has an average score of 3,21 in the Good category and 3,28 for women in the Good category; (3) there is no significant difference in the attitudes of students of biology, chemistry, physics education study programs towards indigenous science-based science learning in songket cloth motifs, as evidenced by the significance value of the Anova test of 0,507>0,05; (4) there is no significant difference in the attitudes of male and female students towards indigenous science-based learning in the songket cloths motifs, as evidenced by the significance value of the t-test of 0,455>0,05.